A Game of Norms: Migrants, Crime and Criminal Justice in Early Modern Bologna - Muurling, Sanne (TSEG - The Low Countries Journal of Social and Economic History, 2023)
While the treatment of migrants in the criminal justice system has recently been designated one of the most relevant research directions in the history of crime, scholarship on the period before the nineteenth century and outside of England or Holland remains far and few between. This article offers a first exploration of the role of offenders’ geographical origins in the administration of criminal justice in an early modern Italian city. It scrutinizes patterns of prosecution and sentencing for three distinct types of crime (pauper mobility, theft, and violence) brought before Bologna’s secular criminal court in the seventeenth and eighteenth century. By doing so, it reveals both the variability of repertoires of inclusion and exclusion across the spectrum of criminalized behaviours, and the different stages at which a migrant past could pose a disadvantage in the personalized game with the norms we call early modern criminal justice.